2018
DOI: 10.1080/13511610.2018.1537844
|View full text |Cite
|
Sign up to set email alerts
|

Capacity-building barriers to S3 implementation: an empirical framework for catch-up regions

Abstract: In this paper, we investigate the implementation challenge of Smart Specialisation Strategies (S3) in catch-up regional environments, through the lens of capacity building. We analyse capacity building at two levels: micro-level (individual organisations) and meso-level (regional inter-organisational networks). We use empirical evidence from 50 interviews conducted in the period 2015-2017 from two Greek regions dramatically hit by the economic crisis (Crete and Central Macedonia). We argue that in the Cretan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 51 publications
2
22
1
Order By: Relevance
“…(RQ 1) What sectors in public services have implemented collaborative governance? (Zubair et al, 2017), (Ward et al, 2018), (Thiarai et al, 2019), (Scott & Gilson, 2017), (Bekker et al, 2018), (Moscou & Kohler, 2017), (Kamugumya & Olivier, 2016), (Kim, 2015), (Jobson et al, 2017), (Rensburg et al, 2018), (Gifford et al, 2017), (Broom et al, 2016), (Bordier et al, 2018), (Addison et al, 2016), (Nóbrega et al, 2018) (Webster & Cheyne, 2017), (Supromin & Choonhakhlai, 2017), (Papamichail et al, 2018), (Galli et al, 2019), (Fathimath, 2017), (Choi & Robertson, 2018), (Brinks, 2018), (Vilkė et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(RQ 1) What sectors in public services have implemented collaborative governance? (Zubair et al, 2017), (Ward et al, 2018), (Thiarai et al, 2019), (Scott & Gilson, 2017), (Bekker et al, 2018), (Moscou & Kohler, 2017), (Kamugumya & Olivier, 2016), (Kim, 2015), (Jobson et al, 2017), (Rensburg et al, 2018), (Gifford et al, 2017), (Broom et al, 2016), (Bordier et al, 2018), (Addison et al, 2016), (Nóbrega et al, 2018) (Webster & Cheyne, 2017), (Supromin & Choonhakhlai, 2017), (Papamichail et al, 2018), (Galli et al, 2019), (Fathimath, 2017), (Choi & Robertson, 2018), (Brinks, 2018), (Vilkė et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…( (Webster & Cheyne, 2017), (Ward et al, 2018), (Thiarai et al, 2019), (Tefera et al, 2019), (Supromin & Choonhakhlai, 2017), (Scott & Gilson, 2017), (Pettersson, 2017), (Papamichail et al, 2018), (Moscou & Kohler, 2017), (Kim, 2015), (Jobson et al, 2017), (Gifford et al, 2017), (Fathimath, 2017), (Wijs et al, 2016), (Brinks, 2018), (Vilkė et al, 2018), (Bekker et al, 2018).…”
Section: Education Sectormentioning
confidence: 99%
“…In parallel, another interrelated-and key-variable should be considered: ERDF allocation for the next period, for the funds will largely support the implementation of the strategy (for the thematic objective on research and innovation). First of all, we must have in mind that not all territories are the same; for instance, regions with a less developed environment often present what was named the European regional innovation paradox, which refers to the fact that they require further funding while they have limited absorptive capacities (Urraya et al, 2018;Muscio et al, 2015;Papamichail et al, 2019). This difference, among other aspects, must be considering when reshaping the proposed ERDF operational programmes, which must be adapted to the territorial context and needs.…”
Section: Challenge 2: What To Keep What To Reshape What To Removementioning
confidence: 99%
“…They emphasize that the analysis of stakeholder networks would allow a better understanding of the implementation of innovation practices, while Foray (2018) highlights that the underlying coordination mechanisms are still rather unexplored. Papamichail et al (2019) investigate regional inter-organizational networks and conclude that the practical S3 implementation challenges also include the capability of regional actors to build inter-organizational networks. Fitjar and Rodríguez-Pose (2011) show how business networks relate to innovativeness and different levels of cooperation, accounting for diversity of partners by geographical and personal distance.…”
Section: Smart Specialisation Coordination and Networkmentioning
confidence: 99%
“…The paper differs in several ways from existing contributions. In contrast to other works on peripheral regions that have applied single or multiple comparative case study approaches (e.g., Papamichail et al, 2019), it applies a mixed-methods triangulation exercise (Bryman, 2003) to S3. Huggins and Prokop (2017) have shown that regional performance can be better understood by accounting for network relationships of local public actors; however, previous work on stakeholder networks has typically neglected that focal actors are characterized by different relational characteristics (Papamichail et al, 2019).…”
Section: Introductionmentioning
confidence: 99%